Hypovolemic shock due to severe gastrointestinal bleeding in a child taking an herbal syrup - Paola Angela Moro; Valerio Flacco; Federica Cassetti; Valentina Clementi; Maria Laura Colombo; Giulia Maria Chiesa; Francesca Menniti-Ippolito; Roberto Raschetti; Carmela Santuccio (Istituto Superiore di Sanità, 2011)
We report the case of a 4-years-old boy who was admitted with hypovolemic shock due to a severe gastrointestinal bleeding. The esophagogastroduodenoscopy (EGDS) showed hiatus hernia, erosions and ulcerations of the lower esophagus, possibly due to a gastroesophageal reflux, and a small duodenal erosion. The child was previously healthy and he had never shown any symptoms related to this condition. The only product taken by the child in the previous days was a syrup containing several herbs, among which Filipendula ulmaria (L.) Maxim. and Salix spp. (known to contain salicylates), marketed as food and prescribed by his paediatrician to treat a mild cold accompanied by fever. Quali-quantitative analysis confirmed the presence of salicylates in the syrup. Naranjo algorithm showed a probable correlation between the onset of symptoms and the consumption of the herbal remedy. The child recovered after receiving intensive care. The product was withdrawn from Italian market.